EXHALTED PRIESTS? MINISTERIAL FORMATION AND THEOLOGY OF THE CROSS - Trisk, Janet (Scriptura, 2007)
following Douglas John Hall, I note that in this article truimphalism rather than a theology of the cross is generally the basis for ecclesial praxis. I then go on to outline a feminist theology of the cross and argue that this theology of the cross should be the foundation of ecclesiology in South Africa at the time. In particular, it should be the basis for theological education and ministerial formation.